STUDI HUBUNGAN KUANTITATIF STRUKTUR-AKTIFITAS (HKSA)SENYAWA TURUNAN 4-AMINOQUINOLIN PIRIMIDIN, DOCKING MOLEKUL, PENELUSURAN FARMAKOFOR, VIRTUAL SCREENING, UJI TOKSISITAS, DAN PROFIL FARMAKOKINETIK SEBAGAI ANTIMALARIA SECARA IN SILICO - Nursalam Hamzah; Afrisusnawati Rauf; Ariwanti Ariwanti (Jurnal Farmasi UIN Alauddin Makassar, 2015)
A research of quantitative structure-activity relationship (QSAR), molecular docking, searching pharmacophore, virtual screening, toxicity test, and Pharmacokinetic Profile of 4-Aminoquinoline Pyrimidine Derivative Compounds as Plasmepsin enzyme inhibitor as Antimalarial by in silico has been conducted. This study aims to find the QSAR model equation of 4-Aminoquinoline Pyrimidine derivative compounds,  to find pharmacophore features of compounds that responsible for inhibition activity of Plasmepsin enzyme in Plasmodium falciparum, as well as to select compounds from virtual screening results then determine the pharmacocinetic profile, and the toxicity of metabolites for malaria treatment. The procedure begins with the modelling and ab initio geometry optimization of the molecular structure by HyperChem 8.0. QSAR descriptors calculation, pharmacophore feature determination and molecular docking are done by using MOE 2009. Furthermore, toxicity testing by Toxtree and AdmetSAR, as well as pharmacokinetic profile determination by using PreADME done to 150.000 natural product compounds from zinc database. From the experiments, the equation obtained: 1/IC50 = 5.3757 + (0.7514 AM1_HOMO) + (-0.3100 log P (o/w)) + (0.0065 vdw_vol), where r2 = 0.9282 dan q2 = 0.9282, beside that molecular docking results for protein code 2IGX compound 13 showed better results with the value of docking score (S) is -129.7491.  As for the compounds of zinc database, the result is a compound with code ZINC32501354 and ZINC32501366 are choosen compound among 150.000 compounds in terms of suitability of the pharmacophore query, docking by pharmacophore method, bioavailability prediction using Lipinski rule of five and from the prediction of ADME/T